"Curated subscription commerce: A theoretical conceptualization". (May 2020) - Bischof, Severin Friedrich; Boettger, Tim M.; Rudolph, Thomas
Abstract: Subscription commerce emerged as an up-and-coming phenomenon in retailing that enables shoppers to automatically receive recurring deliveries of consumer goods. One important dimension along which subscription services differ is the degree to which the content of each delivery is surprising. This paper focuses on two archetypes at opposite ends of this dimension, namely predefined and curated surprise subscriptions, and juxtaposes them to conceptualize surprise as a retail mechanism. It is hypothesized that curated surprise subscriptions carry an inherent risk to receive unappealing products, as consumers outsource the decision-making process to the subscription provider, which can influence consumers' choices and attitudes. Three studies explore the role of risk perception in consumers' evaluation of consumer goods subscriptions. First, it was found that consumers prefer shorter delivery intervals for predefined subscriptions and longer delivery intervals for curated surprise subscriptions, in line with Prospect Theory. Second, empirical evidence for perceived risk as a mediating variable in this relation is provided. Finally, it is shown how retailers can manipulate associated risk through the introduction of a free-return option. The article is concluded by introducing a new typology of subscription services and discussing implications for managerial practice as well as avenues for future research.